2017
DOI: 10.2147/ndt.s140091
|View full text |Cite
|
Sign up to set email alerts
|

The regional neuronal activity in left posterior middle temporal gyrus is correlated with the severity of chronic aphasia

Abstract: BackgroundAphasia is one of the most disabling cognitive deficits affecting >2 million people in the USA. The neuroimaging characteristics of chronic aphasic patients (>6 months post onset) remain largely unknown.ObjectiveThe objective of this study was to investigate the regional signal changes of spontaneous neuronal activity of brain and the inter-regional connectivity in chronic aphasia.Materials and methodsResting-state blood oxygenation level-dependent functional magnetic resonance imaging (fMRI) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 25 When positron emission technology was used to analyze the semantic processing of words, the ITG showed obvious activation. 26 Correspondingly, when the ITG is damaged in patients with aphasia, there are often semantic defects, 27 and some studies have observed ITG atrophy in semantic dementia, 28 which supports their participation in semantic language understanding. Through meta-analysis connectivity research of the ITG, it was found that, although the ITG participates in language processing, it cannot be considered as the core language processing area, and it can be understood as a kind of language processing edge area.…”
Section: Discussionmentioning
confidence: 91%
“… 25 When positron emission technology was used to analyze the semantic processing of words, the ITG showed obvious activation. 26 Correspondingly, when the ITG is damaged in patients with aphasia, there are often semantic defects, 27 and some studies have observed ITG atrophy in semantic dementia, 28 which supports their participation in semantic language understanding. Through meta-analysis connectivity research of the ITG, it was found that, although the ITG participates in language processing, it cannot be considered as the core language processing area, and it can be understood as a kind of language processing edge area.…”
Section: Discussionmentioning
confidence: 91%
“…Brodmann area 21 [middle temporal gyrus (MTG)] is implicated in sound recognition as well as word and picture semantic processing 74 , language processing 75 , decoding gaze direction, deductive reasoning 76 plus intelligible speech and processing of verbal mental arithmetic 77 . Brodmann area 40 (supramarginal gyrus) plays a role in visual word recognition, auditory memory processing, and emotion recognition 78 80 .…”
Section: Resultsmentioning
confidence: 99%
“…The temporal lobe has always been considered as an important region for semantic processing and sentence production, and comprehension defificits were associated with lesions in the temporal lobe, including the anterior and posterior superior temporal gyri (aSTG, pSTG), the anterior and posterior middle temporal gyri (aMTG, pMTG), the auditory association areas [planum temporale (PT) and planum polare (PP)], the temporal pole (TP), the MTG temporooccipital (toMTG) regions, superior marginal gyrus (SMG), angular gyrus (AG), CO and PO. Li et al (45) found that the regional neuronal activity in left pMTG was correlated with the severity of chronic aphasia. Sebastian and his colleagues (46) observed four aphasia patients due to posterior cerebral artery stroke and found that improved naming skills were associated with increased FC within and between the left and right hemispheres language regions (IFG, STG, MTG, inferior temporal gyrus (ITG), SMG and AG), while the patients of whom the language function did not improve showed an opposite pattern.…”
Section: Discussionmentioning
confidence: 99%